Photosynthesis and food security: the evolving story of C4 rice - Furbank, R; Kelly, S; von Caemmerer, S (Springer, 2023)
Traditional “Green Revolution” cereal breeding strategies to improve yield are now reaching a plateau in our principal global food crop rice. Photosynthesis has now become a major target of international consortia to increase yield potential. Synthetic biology is being used across multiple large projects to improve photosynthetic efficiency. This review follows the genesis and progress of one of the first of these consortia projects, now in its 13th year; the Bill and Melinda Gates funded C4 Rice Project. This project seeks to install the biochemical and anatomical attributes necessary to support C4 photosynthesis in the C3 crop rice. Here we address the advances made thus far in installing the biochemical pathway and some of the key targets yet to be reached.